Infection control: effect of nursing teaching protocol on nurses’ knowledge and practice regarding kidney transplantation patients - Mohamed Younis, Hanan; Thabet Mohammed, Ghada; Sayed Khalil, Shaymaa (International Journal of Advanced Nursing Studies, 2018)
Aims: Assess nurses' knowledge & practice about infection control regarding kidney transplantation patients, design and implement of nursing teaching protocol regarding kidney transplantation patients, & assess the effect of nursing teaching protocol on nurses knowledge and practice about infection control regarding kidney transplantation patients. The study was conducted in the kidney transplantation unit of Assiut Nephrology Hospital; data were collected from all nurses working in Kidney Transplantation Unit (30 nurses). Three tools used for data collection; Pre-posttest interview questionnaire sheet & observation checklist sheet, & Nursing teaching protocol.Results: all the nurses were female, most of them their ages were from 18 - 25 years, single, living in the rural area, had a high degree in nursing. Most of them had previous infection-control training. An improvement in the mean knowledge & practice scores were found after the application of the teaching protocol (1st hypothesis). A positive correlation between nurse's knowledge and practice scores after application of the nursing teaching protocol (2nd hypothesis).Conclusions: Improving nurse's knowledge and practice can favorable affect the incidence and outcome of kidney transplantation patients.Recommendations: There is a need for continued and written standards training programs about infection control regarding kidney transplantation patients and should be available.